2016
DOI: 10.1177/0093650214555180
|View full text |Cite
|
Sign up to set email alerts
|

Self-Affirmation Before Exposure to Health Communications Promotes Intentions and Health Behavior Change by Increasing Anticipated Regret

Abstract: Health-risk information can elicit negative emotions like anticipated regret that may positively affect health persuasion. The beneficial impact of such emotions is undermined when target audiences respond defensively to the threatening information. We tested whether self-affirming (reflecting on cherished attributes) before message exposure can be used as strategy to enhance the experience of anticipated regret. Women were self-affirmed or not before exposure to a message promoting fruit and vegetable consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
(127 reference statements)
1
23
0
Order By: Relevance
“…Epton & Harris, 2008;Epton, Harris, Kane, van Koningsbruggen & Sheeran, 2014) as well as in other domains (Cohen & Sherman, 2014). In particular, regarding the food consumption topic of the present study, self-affirmation manipulations have been shown to be effective, for example, in promoting fruit and vegetable consumption (Epton & Harris, 2008;Harris et al, 2014;Pietersma & Dijkstra, 2011;van Koningsbruggen et al, 2014), avoidance of unhealthy foods (Cornil & Chandon, 2013), and weight loss (Logel & Cohen, 2012). Some of this research has combined a self-affirmation intervention with health-related information (e.g., Epton & Harris, 2008) while some of it has not (Cornil & Chandon, 2013;Logel & Cohen, 2012); different methodological approaches might be expected to result in different patterns of findings since, for example, (and while acknowledging, of course, that threat may be implicit and/or explicit) the core literature on self-affirmation processes points to the important component of threat in eliciting selfaffirmation effects.…”
Section: Restrained Eatersmentioning
confidence: 76%
“…Epton & Harris, 2008;Epton, Harris, Kane, van Koningsbruggen & Sheeran, 2014) as well as in other domains (Cohen & Sherman, 2014). In particular, regarding the food consumption topic of the present study, self-affirmation manipulations have been shown to be effective, for example, in promoting fruit and vegetable consumption (Epton & Harris, 2008;Harris et al, 2014;Pietersma & Dijkstra, 2011;van Koningsbruggen et al, 2014), avoidance of unhealthy foods (Cornil & Chandon, 2013), and weight loss (Logel & Cohen, 2012). Some of this research has combined a self-affirmation intervention with health-related information (e.g., Epton & Harris, 2008) while some of it has not (Cornil & Chandon, 2013;Logel & Cohen, 2012); different methodological approaches might be expected to result in different patterns of findings since, for example, (and while acknowledging, of course, that threat may be implicit and/or explicit) the core literature on self-affirmation processes points to the important component of threat in eliciting selfaffirmation effects.…”
Section: Restrained Eatersmentioning
confidence: 76%
“…physical, nutritional and pharmacological [102]. in the wider health psychology literature, the role of self-efficacy, and pre-intervention self-affirmation to support self-efficacy, is evidenced as important in improving adherence to new healthy lifestyle behavior changes, supporting its potential use in frailty interventions [103].…”
Section: Other Interventionsmentioning
confidence: 99%
“…One public health study that also reported no group effect on intention but observed an effect on behaviour change, established that Response Efficacy, the belief that undertaking the required behaviour will result in desirable outcomes and therefore remove the imminent threat, mediated the effects of selfaffirmation (Epton & Harris, 2008). Van Koningsbruggen demonstrated that anticipated regret mediated the effects of self-affirmation on intentions (van Koningsbruggen et al, 2014). Stress reduction or mood enhancement is also a likely consideration which should be assessed in future studies (Cohen & Sherman, 2014).…”
Section: Evaluation Of the Health Risk Informationmentioning
confidence: 99%
“…Therefore it was unclear what had led to the observed clinical effect. It is possible that the effects of self-affirmation might have arisen due to hidden mediators not assessed in the study such as stress reduction (Logel & Cohen, 2012), response efficacy (Epton & Harris, 2008) or anticipated regret (van Koningsbruggen et al, 2014) and it is acknowledged that more research is needed to investigate this further. However, it was also considered that patients might not have ranked phosphate treatment high on their priorities compared with other, more demanding, aspects of treatment and this might have been reflected in the responses such as psychological threat (Karamanidou, Weinman, & Horne, 2013).…”
mentioning
confidence: 99%